The Influence of the Hot Brain Program on Improving Interpersonal Intelligence and Mathematical Logic in Elementary School Students - Landriani Nurdin; Hendri Marhadi; Muhammad Fendrik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The schoolyard is one of the learning facilities with great potential to be utilized as an active learning space, but in reality, its utilization is still low, which impacts the suboptimal development of interpersonal and mathematical-logical intelligence in elementary school students. This study aims to analyze the influence of the HOT BRAIN program, which is a learning model based on the use of open school spaces, on improving students' interpersonal and mathematical logical intelligence. The research used a quantitative approach with a quasi-experimental pretest-posttest control group design. The study involved two classes: one experimental class that received the HOT BRAIN program treatment and one control class that did not receive the HOT BRAIN program treatment. The research results showed that the experimental group experienced a significant increase in interpersonal intelligence (Sig. < 0.001) and mathematical-logical intelligence (Sig. < 0.001) compared to the control group, thus confirming that the HOT BRAIN program is more effective than conventional learning. In conclusion, the HOT BRAIN program has a positive and significant impact on developing interpersonal and mathematical-logical intelligence in elementary school students thru game-based learning activities, exploration, and social interaction in the open school environment.